THE JOURNEY TO REDEMPTION: A STUDY OF THE VIOLENCE IN NORMAN MAILER’S THE NAKED AND THE DEAD - Lingpo Zhang (Universitas Islam Sumatera Utara (UISU), 2018)
The Naked and the Dead, as Norman Mailer’s first and representative work, is not only the most classical war fiction, but also the most controversial work since World War II. The war is used as a background to explore various problems emerging in American society. Throughout history, violence has always played an important part in human development, and promoted the development of human society. War as the extreme manifestation of violence causes great significance on human history. During the time of World War Two, people lives under the shadow of totalitarianism, the situation is especially serious in the U.S. Army. Some of the soldiers are transformed to war machines with neither personal will nor identity. In Mailer’s mind, violence and creativity have a twin-like relation, if we cut all the violence out of society, we also cut out all the creativity, and violence becomes the resolution which people employ with to regain their humanity, so as to have self-redemption. Croft’s failure of conquering Mount Anaka fully revels there is still possibility that human can be redeemed.